filmov
tv
Prove that `sin^(-1)(63/65)=sin^(-1)(5/13)+cos^(-1)(3/5)`
Показать описание
Doubtnut
Рекомендации по теме
0:03:43
Prove that `sin^(-1)(63/65)=sin^(-1)(5/13)+cos^(-1)(3/5)`
0:01:07
Prove tan-1 63/16 = sin-1 5/13 + cos-1 3/5
0:03:28
Prove that: `tan^(-1)(63)/(16)=sin^(-1)5/(13)+cos^(-1)3/5`...
0:00:31
#shorts # sin^-1(5/13)+cos^-1(3/5)=sin^-1(63/65)
0:01:01
Prove tan⁻¹ 63/16 = sin⁻¹ 5/13 + cos⁻¹ 3/5
0:06:58
Class 12 Inverse Trigonometric Functions. Prove that:- sin^-1(5/13) + cos^-1(3/5) = sin^-1(63/65)
0:03:46
Prove that: `cos^(-1)(12)/(13)+sin^(-1)3/5=sin^(-1)(56)/(65)`...
0:06:18
Prove that tan inverse 63 by 16 is equal to sin inverse 5 by 13 + cos inverse 3 by 5
0:01:08
Prove cos-1 12/13 + sin-1 3/5 = sin-1 56/65
0:06:12
Inverse trigonometric functions: Sin-1(3/5)+Cos-1(12/13)=Cos-1(33/65)@EAG
0:05:59
Miscellaneous Exercise on Chapter 2 Question 7,Prove that:tan^(-1) 63/16 =sin^(-1) 5/13+cos^(-1) 3/5
0:02:42
Prove that tan^-1(63/16) = sin^-1(5/13) + cos^-1(3/5) .
0:06:49
'The value of `sin^(-1)((12)/(13)) - sin ^(-1)((3)/(5))` is equal to (A) `pi-sin ^(-1) ((63)/(6...
0:06:40
prove that tan inverse 63/16 equal to sin inverse 5/13 + cos inverse 3/5
0:01:00
Prove cos⁻¹ 12/13 + sin⁻¹ 3/5 = sin⁻¹ 56/65
0:03:49
XII Inverse Trigonometric Functions Show that sin^ 1 5 13 + cos^ 1 3 5 = tan^ 1 63 16
0:03:31
sin^-1(12/13)+cos^-1(4/5)+tan^-1(63/16)=π l Ex 11 Chapter 2 Inverse Trigonometry CBSE-12th JEE
0:05:13
Prove that: `sin^-1(3/5)-cos^-1(12/13)=sin^-1(16/65)`
0:03:17
Show that `sin^(-1)\'5/13+cos^(-1)\'3/5=tan^(-1)\'63/16`.
0:01:57
Explain why cos^-1(5/13)=sin^-1(12/13)=tan^-1(12/5)
0:07:22
Show that `sin^-1 (3/5)+cos^-1(12/13)=cos^-1(33/65)=sin^-1(56/65)`
0:08:24
Prove that sin^-1(3/5)-cos^-1(12/13)=sin^-1(16/65)
0:12:38
Important Question for 12th Board ||Prove that: sin inverse 5/13 + cos inverse 3/5=tan inverse 63/16
0:04:16
sin^-1(4/5) + sin^-1(5/13) + sin^-1(16/65) = π/2